Analisis Pengendalian Kualitas Produk Iqro Kustom dengan Menggunakan PDCA (Plan-Do-Check-Act) (Studi Kasus: CV Alquran Nuzula) - Dimas Adi Prayitno; Herlina Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
CV Alquran Nuzula is a printing company that produces custom Iqro books using a Make-to-Order (MTO) system. The company faced a high product defect rate exceeding the company standard of ≤1%, with the defect percentage ranging from 2.39% to 3.10% from August 2025 to February 2026. This study aimed to identify the causes of defects, analyze the application of the PDCA (Plan-Do-Check-Act) method in quality control, and determine the level of defect reduction after implementing improvements. The method used was PDCA combined with the Seven Tools of Quality Control: histograms, Pareto diagrams, fishbone diagrams, and control charts (P-Charts). The research data were obtained from production data and defective product data from August 2025 to February 2026 through observation, interviews, and company documentation. The results showed that the dominant types of defects were insufficient lamination at 58.15% and uneven glue at 24.28% of the total defects. The main causal factors come from human, machine, material, method, and environmental aspects. Implementation of improvements through PDCA (Defect Management Process) in the form of machine maintenance, SOP and checklist development, operator training, and material control has proven effective in reducing the defect rate. The average number of defects decreased from 45 units to 18 units per month, while the cost of quality failure decreased from Rp416,500 to Rp111,500 per month, representing a savings of 73%. These results indicate that the PDCA method is effective in improving the quality of Iqro Kustom products at CV Alquran Nuzula.